PENERAPAN METODE ADAPTIVE MEDIAN FILTER UNTUK MEREDUKSI NOISE PADA CITRA X-RAY - Wika Elsa Pratiwi; Fince Tinus Waruwu (STMIK Budi Darma, 2018)
The problem often faced by radiologists in analyzing thorax fractures through manual x-ray images and requiring a longer time to study the image and radiologists also often have difficulty reading x-ray images that have noise when shooting x-ray and can lead to difficulties in diagnosis. The adaptive median filter method is a suitable problem-solving technique. In the improvement of the quality of the x-ray image, the x-ray image must first be converted into the pixel image value, to get the pixel value from the x-ray image. -ray then determine the matrix value to get the maximum, minimum, median and pixel coordinate values. Then determine whether the pixel value will be replaced with a median value, if not noise then the pixel value is not replaced. The end result of this system is in the form of design in reducing noise on x-ray imagery which is used as an aid in analyzing x-ray images. This system will help radiologists in reading images.Keywords: X-ray image, noise reduction, adaptive median filter